A comparative study on the stress distribution around dental implants in three arch form models for replacing six implants using finite element analysis - Maryam Zarei; Mahmoud Jahangirnezhad; Hojatollah Yousefimanesh; Maryam Robati; Hossein Robati (Wolters Kluwer Medknow Publications, 2018)
Background: Dental implant is a method to replacement of missing teeth. It is important for replacing the missed anterior teeth. In vitro method is a safe method for evaluation of stress distribution. Finite element analysis as an in vitro method evaluated stress distribution around replacement of six maxillary anterior teeth implants in three models of maxillary arch. Materials and Methods: In this in vitro study, using ABAQUS software (Simulia Corporation, Vélizy-Villacoublay, France), implant simulation was performed for reconstruction of six maxillary anterior teeth in three models. Two implants were placed on both sides of the canine tooth region (A model); two implants on both sides of the canine tooth region and another on one side of the central incisor region (B model); and two implants on both sides of the canine tooth region and two implants in the central incisor area (C model). All implants evaluated in three arch forms (tapered, ovoid, and square). Data were analyzed by finite analysis software. Results: Von Mises stress by increasing of implant number was reduced. In a comparison of A model in each maxillary arch, the stress created in the cortical and cancellous bones in the square arch was less than ovoid and tapered arches. The stress created in implants and cortical and cancellous bones in C model was less than A and B models. Conclusions: The C model (four-implant) reduced the stress distribution in cortical and cancellous bones, but this pattern must be evaluated according to arch form and cost benefit of patients.